Closing the Loop: Engineering Customer-Centric Products Using Support Logs and CSAT Signals - Mukul Garg, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Integrating customer support logs, tickets, product telemetry, and CSAT feedback through data engineering pipelines enables systematic identification of user pain points. Automated issue tagging (85-92% accuracy) combined with sentiment analysis and usage correlation reduces critical bug resolution time by 30-40% and increases positive CSAT sentiment by 15-25% within six months. Case studies confirm that demonstrating feedback-driven improvements to customers raises future CSAT response rates by 12-18% and boosts feature adoption by 20% compared to intuition-based roadmaps (Chen et al., 2023).
Keywords: Support Analytics; CSAT Correlation; Product Telemetry; NLP Classification; Data Pipelines